Les développements récents de la macroéconomie post-keynésienne - Angel Asensio; Sébastien Charles; Dany Lang; Edwin Le Heron (Revue de la Régulation)
The purpose of this article is to show why recent developments in post-Keynesian modeling are valuable to understand the functioning of contemporary capitalism and to limit its dysfunction. First, the main methodological innovations from the last decade are emphasized: endogenous money, the role of banks and of financial system, formalization of path-dependency and long-run dynamics and stock flow consistent models. Second, we study the developments involved by Kalecki’s works on dynamic analysis and the interaction between growth and income distribution. Finally, the importance of active and demand oriented macro-policies is underlined in order to promote a new regulation of capitalism, more efficient and fair than financialized capitalism.